Safety of inactivated SARS-CoV-2 vaccines in myasthenia gravis: A survey-based study - Li, Hong-Yan; Shao, Li-Yuan; Song, Min; Hu, Shi-Min; Yue, Yao-Xian; Li, Hai-Feng (Frontiers in Immunology, 2022)
Background: Vaccination remains the most effective measures to prevent SARS-CoV-2 infection and worse outcomes. However, many myasthenia gravis (MG) patients are hesitant to receive vaccine due to fear of worsening. Methods: MG patients were consecutively enrolled in two MG centers in North China. The “worsening” after vaccination was self-reported by MG patients, and severity was measured with a single simple question. General characteristics and disease status immediately prior to 1st dose were compared between the worsening and non-worsening groups. Independent factors associated with worsening were explored with multivariate regression analysis. Results: One hundred and seven patients were included. Eleven patients (10.3%) reported worsening after vaccination, including 8 patients with mild or moderate worsening and 3 patients with severe worsening. Only one of them (0.9%) needed escalation of immunosuppressive treatments. There were significant differences between the worsening and non-worsening groups in MGFA classes immediately before the first dose and intervals since last aggravation. Precipitating factors might contribute to the worsening in some patients. Logistic regression revealed that only interval since last aggravation ≤ 6 months was associated with worsening after SARS-CoV-2 vaccination (P=0.01, OR=8.62, 95%CI:1.93-38.46). Conclusion: SARS-CoV-2 vaccines (overwhelming majority was inactivated vaccines) were found safe in milder Chinese MG patients who finished two doses. Worsening after vaccination was more frequently seen in patients who was presumed as potential unstable (intervals since last aggravation ≤ 6 months). However, mild worsening did occur in patients who was presumed to be stable. Precipitating factors should still be sought and treated for better outcome.